Case report: A case of unilateral combined central retinal vein occlusion, incomplete central retinal artery occlusion, and papillitis following a third dose of COVID-19 vaccination - Furukawa, Ami; Suzuki, Yukihiko; Nozuki, Narumi; Kurosaka, Naruki; Kogawa, Satomi; Hara, Shinya; Ueno, Shinji (Frontiers in Ophthalmology, 2024)
Purpose: To present a case of severe visual loss due to retinal arteriovenous occlusion and papillitis in one eye following vaccination against coronavirus infection (COVID-19). Methods: A 45-year-old man undergoing treatment for hypertension noted severely reduced visual acuity in the right eye one day after receiving the third dose of a COVID-19 vaccine manufactured by Moderna. Clinical examination findings showed that the best corrected visual acuity for the right eye was counting fingers. Other findings included a circumferential retinal hemorrhage, perimacular ischemic color, severe macular edema, and severe optic disc swelling, indicating the presence of central retinal vein occlusion, incomplete central retinal artery occlusion, and papillitis. Based on the possibility of post-vaccination inflammation and/or abnormal immune response, three courses of steroid pulse therapy were given and visual acuity was slightly improved to 20/1000. Results: Three months after onset of symptoms, the macular edema had disappeared, while conversely, retinal thinning of the macula and extensive non-perfusion areas mainly on the nasal side were noted. Conclusion: Findings in this case suggest that inflammation and abnormal immune response developing after receiving a COVID-19 vaccination may lead to combined retinal arteriovenous occlusion and papillitis.